2012
DOI: 10.1136/acupmed-2011-010121
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auricular Acupressure Combined with Low-Calorie Diet on the Leptin Hormone in Obese and Overweight Iranian Individuals

Abstract: Background Human leptin is a peptide hormone that is released from white adipocytes. The absence of leptin or its receptor leads to uncontrolled food intake, leading to obesity. In the present work, the effects of auricular acupressure combined with low-calorie diet on the leptin hormone level were investigated. Methods Volunteers (n=86) with body mass indices (BMI) between 25 and 45 kg/m 2 were randomised into a case (n=43) or a control (n=43) group. Participants in each group received a low-calorie diet for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 30 publications
1
37
0
16
Order By: Relevance
“…Main characteristics of included RCTs were shown in Table 1 . The participants were from Australia [ 28 ], the United States [ 26 ], Turkey [ 46 ], Korea [ 51 ], Iran [ 36 ], Egypt [ 48 ], and China. Age of participants ranged from 15 to 70 years, while the sample size of the studies ranged from 12 to 86.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Main characteristics of included RCTs were shown in Table 1 . The participants were from Australia [ 28 ], the United States [ 26 ], Turkey [ 46 ], Korea [ 51 ], Iran [ 36 ], Egypt [ 48 ], and China. Age of participants ranged from 15 to 70 years, while the sample size of the studies ranged from 12 to 86.…”
Section: Resultsmentioning
confidence: 99%
“…Ten RCTs [ 26 – 28 , 31 , 32 , 35 , 36 , 38 , 39 , 45 ] reported adverse events, while no major complications were noticed in all included studies. Three included studies [ 35 , 36 , 39 ] reported that no adverse effects were noted in both experimental group and placebo group. In one included RCT, there were two patients reporting mild ecchymosis and one abdominal discomfort case reported as adverse events after electroacupuncture treatment; no case was reported in the lifestyle modification group [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…En ninguno de los grupos se encontró cambios en relación a las variables antropométricas aunque en ambos el promedio de kilogramos disminuyó marginalmente, similar a los resultados presentados por Hsu et al (29) , Lien et al (30) , y Ruan et al (31) . Sin embargo, difieren con otros estudios donde se ha presentado una reducción significativa de peso y/o masa grasa en sujetos tratados con auriculopuntura (32)(33)(34) . En relación al control de peso o masa grasa, autores sugieren que el posible mecanismo de acción por la cual la auriculopuntura pudiese actuar es a través de una reducción de la insulina y leptina e incremento de la grelina, colecistoquinina y la expresión del neuropéptido Y (35)(36)(37) .…”
Section: Discussionunclassified
“…12,54,60,64 For the RCTs with multiple treatment sessions, the frequency of earacupuncture or electro/laser ear-acupuncture was from one session within 30 days 19 to one session each day, 29 while the ear-acupressure pellets/seeds were pressed three to five times a day 42,51,52,55,58,60,62,64,66 or as needed. 38,47,67 De qi sensation was mentioned in two RCTs. 55,58 The characteristics of the included studies are summarized in Table 1.…”
Section: Description Of Included Studiesmentioning
confidence: 99%